321 Cancer risk with topical pimecrolimus and tacrolimus for atopic dermatitis: systematic review and Bayesian meta-analysis. (25th January 2023) - Chu, Alexandro W L; Devasenapathy, Niveditha; Wong, Melanie; Srivastava, Archita; Ceccacci, Renata; Lin, Clement; MacDonald, Margaret; Wen, Aaron; Steen, Jeremy; Levine, Mitchell; Pyne, Lonnie; Wang, Julie; et al.
Abstract: Atopic dermatitis affects millions worldwide and is effectively managed by topical treatments, including topical calcineurin inhibitors, pimecrolimus and tacrolimus. In 2005 and 2011, the FDA released reviews associating topical calcineurin inhibitors with a theoretical cancer risk, albeit an uncertain association. We systematically reviewed the risk of cancer in patients with atopic dermatitis exposed to topical calcineurin inhibitors. We systematically identified randomized controlled trials, comparative, and non-comparative non-randomized studies from database inception to 6 June 2022, from MEDLINE, EMBASE, GREAT, LILACS, ICTRP, FDA, EMA, company registers and relevant citations. We included studies in any language addressing the risk of cancer in patients with atopic dermatitis exposed to topical calcineurin inhibitors for greater than 3 weeks. We excluded split-body studies. We conducted a Bayesian meta-analysis and used the GRADE approach to determine the certainty of the evidence. A multidisciplinary panel including patients, advocacy groups and care providers, set an a priori threshold of 1 in 1000 risk difference as a clinically important effect. We analysed 121 studies (52 randomized controlled trials and 69 non-randomized studies) including 3.4 million patents followed for a mean of 11 months (range: 0.7–120). The absolute risk of any cancer with topical calcineurin inhibitor exposure was neither different from controls (absolute risk 4.70 per 1000 with topical calcineurin inhibitor exposure vs. 4.56 per 1000 without; odds ratio 1.03 [95% credible interval 0.94–1.11], moderate-certainty evidence) nor the general US population (4.6 per 1000). Findings were similar in infants, children, and adults, and were robust to trial sequential, subgroup and sensitivity analyses. Among infants, children and adults with atopic dermatitis, moderate-certainty evidence shows that topical calcineurin inhibitors do not increase the risk of cancer. These findings support the safe use of topical calcineurin inhibitors in the management of patients with atopic dermatitis. Our findings provide actional information to inform updated clinical practice guidelines, product labels and continuing education for care providers, to clarify the safe usage of topical calcineurin inhibitors.